The Role of Musawah (Symmetric) Information Partnership on Financial Performance of Sharia BPR - Sukamto; Mislan Cokrohadisumarto, Widiyanto bin; Riawan; Mohamad Sodikin (International Journal of Economics, Management and Accounting, 2023)
Asymmetric information is still a significant concern in the profit and loss sharing financing in Islamic banking, including Sharia Rural Banks (Bank Pembiayaan Rakyat Shariah/Sharia BPR) in Indonesia. This study aims at building a model that can reduce asymmetric information in profit and loss sharing financing by including the musawah information partnership variable to improve sustainable financial performance of sharia BPRs. This study used 115 sharia BPRs in Indonesia as its sample. The results show that musawah information partnership has a strong correlation with financing risk, whereby the higher the musawah information partnership, the lower the financing risk would be. This means that musawah information partnership can help reduce asymmetric information and, eventually, minimize financing risk and improve financial performance. Information quality, musawah information partnership, and financing risk also strongly influenced financial performance both separately and collectively on implementation of profit and loss sharing mechanism in Sharia BPRs. This research has its own theoretical contribution. First, it provides new insights into the value of tawhid as the basis for equal, mutually supportive and mutually beneficial partnerships, ease of access to information and reliable and objective information sharing. Second, the musawah information partnership concept adds a new partnership characterized by Islamic equality values. Third, this research enriches the literature on application of Islamic values, especially the values of musawah in partnership.